Analisis Network Pharmacology Senyawa Metabolit Sekunder Tumbuhan Benalu Kopi (Loranthus ferrugineus Roxb.ex Jack Danser) pada Penyakit Kanker Payudara - Nur Aira Juwita; Wawan Sujarwo; Dinda Rizka Manurung (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to evaluate the potential of coffee bean metabolite compounds as breast anticancer agents through a network pharmacology approach. The method used starts from literature study and PubChem database. Selection of compound eligibility was carried out with SwissADME using Lipinski's Rule of Five criteria. Protein target prediction was done through SwissTargetPrediction, while breast cancer target data was obtained from GeneCards and OMIM. Protein-protein interactions were analyzed with STRING and visualized using Cytoscape. Compound-protein interactions were analyzed through STITCH. The results showed that nine metabolite compounds from coffee bean met the pharmacokinetic criteria, with five main compounds showing anticancer potential is quercetin, oleic acid, linoleic acid, GCG, and PPARA. Protein interaction network analysis identified five central target proteins: IL6, TNF, AKT1, PTGS2, and ESR1. The compound-protein interactions suggest multitarget potential in the modulation of breast cancer-related molecular pathways. Keywords: Breast Cancer, Loranthus ferrugineus, Network Pharmacology